Minimal Residual Disease in Neovascular Age-Related Macular Degeneration - Siedlecki, Jakob; Pulido, Jose; Priglinger, Siegfried (Klinische Monatsblätter für Augenheilkunde, 2021)
With the advent of long-acting anti-vascular endothelial growth factor substances, “healing of AMD (age-related macular degeneration)” might be easily assumed due to prolonged treatment intervals. Adoption of the oncological concept of minimal residual disease for quiescent choroidal neovascularization (CNV) lesions might enhance the importance of continued monitoring, and spur research into the core of the disease, i.e., CNV biology.
Keywords: minimal residual disease; complete remission; age-related macular degeneration; AMD; choroidal neovascularization; CNV